2016
DOI: 10.4236/ijaa.2016.64030
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Review of the Amati Relation for GRBs

Abstract: Gamma-ray bursts (GRBs) are the most powerful explosions in the universe. Although the exact mechanism behind these explosions remains elusive, GRBs hold great promise as cosmological probes for two main reasons: they have been observed up to very high redshift (z > 9), and their gamma-ray emission is unencumbered by any intervening dust. Several GRB energy and luminosity indicators have been discovered. These indicators correlate an observable quantity, like the intrinsic peak energy, E p,i , in the νF ν spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…In Amati's original study [5], the following values were obtained: m ≈ 0.5 and K ≈ 95. However, more recent studies [23] [24] [25] [26] [27] found mean values of <m> = 0.45 and <K> = 141. Another important peak-energy correlation is the Ghirlanda relation, which is a correlation between the peak energy and the total energy corrected for beaming, E γ , which is given by: ( )…”
Section: Peak Energy Correlations and The Amati Relationmentioning
confidence: 99%
“…In Amati's original study [5], the following values were obtained: m ≈ 0.5 and K ≈ 95. However, more recent studies [23] [24] [25] [26] [27] found mean values of <m> = 0.45 and <K> = 141. Another important peak-energy correlation is the Ghirlanda relation, which is a correlation between the peak energy and the total energy corrected for beaming, E γ , which is given by: ( )…”
Section: Peak Energy Correlations and The Amati Relationmentioning
confidence: 99%